STUDY ON PHOTOCATALYTIC REDUCTION OF CU(II) IONS BY UV LIGHT AND TiO2 - , Endang Tri Wahyuni, Mudasir, and Nurul Hidayat Aprilita ([Yogyakarta] : Fak. MIPA Universitas Gadjah Mada, 2007)
Photoreduction of Cu(II) ion in the solution in the presence of UV light and TiO2 photocatalyst has been studied, in which the influences of reaction time, photocatalyst mass, concentration of Cu(II), and solution pH on the effectiveness of the reduction have also been evaluated. Photoreduction was carried out by batch system in a closed reactor equipped with UV lamp having wavelength 300-400nm. The research results indicated that the presence of TiO2 could improve the photoreduction of Cu(II) ion into Cu metal deposited on the TiO2 surface. The improvement was proportional with the increase of TO2 mass, but no improvement was observed when the mass was further increased. The photoreduction increased as the reaction time was extended, but further extension gave no different effect. Increasing pH from 1-5 could enhance of Cu(II) reduction, and further increase of pH from 5-14 could transfer all of the ions from the solution due to precipitate of Cu(OH)2. The photoreduction enhanced with the increase of the initial concentration of Cu(II) but the photoreduction declined when the initial concentrations were further increased. The highest photoreduction of Cu(II) was reached, ca 20%, when 50 ml of Cu(II) 10ppm at pH 3 with 20 mg TiO2 for 24h of the reaction time, was employed. The effectiveness of Cu(II) photoreduction obtained was still low, and so improvement, i.e. by addition of organic acid as reducing agent is suggested.